Synthesis of perfectly sulfonated sodium polystyrene sulfonate over a wide molar mass range via reversible‐deactivation radical polymerization. Issue 14 (31st May 2019) - Balding, Paul; Cueto, Rafael; Russo, Paul S.; Gutekunst, Will R.
ABSTRACT: An aqueous reversible‐deactivation radical polymerization (RDRP) approach is used to synthesize sodium polystyrene sulfonate directly from functionalized monomers to give uniformly and completely sulfonated materials. Reproducible gram scale syntheses are achieved under simple one pot reaction conditions at ambient temperatures, and full monomer conversions are achieved within approximately 3 h. Reaction variables such as pH, sodium chloride concentration, and methanol cosolvent have a significant effect on the molecular weights ( M n ≈ 20, 000–400, 000 g·mol −1 ) obtained by gel permeation chromatography coupled multiangle light scattering. Observed dispersities were reasonably narrow: Ð ≈ 1.05–1.3. A parametric optimization, rather than direct variation of the monomer to initiator ratio, resulted in some of the highest molecular weight polymers by an RDRP approach. Linear progression between M n and monomer conversion occurs at a neutral reaction pH, which results in narrow polymer molecular weight distributions, along with high end‐group fidelity as demonstrated with chain extension reactions. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1527–1537 Abstract : Sodium polystyrene sulfonate was synthesized on gram scales via an aqueous reversible‐deactivation radical polymerization (RDRP) approach. Reaction pH, MeOH cosolvent, and added sodium chloride were varied, rather than a traditional M:I ratio, to target a range of many different molecular weights ( M n 20–400 kDa), with reaction control, repeatability, chain end fidelity, and low dispersities exhibited ( Ð < 1.3). These polymers exhibit some of the highest molecular weights achieved by an aqueous RDRP approach.